2021
DOI: 10.1002/pchj.475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uncertainty‐dependent residential mobility on loss aversion

Abstract: The current research aimed to examine the relationship between residential mobility and loss aversion, a ubiquitous decisionmaking bias conceptualized in prospect theory. Combining correlational, experimental, and electroencephalography approaches, we tested the hypothesis that residential mobility may increase loss aversion. The results revealed a positive correlation between residential mobility and loss aversion (Study 1). These effects were moderated by individuals' residential mobility/stability mindsets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Previous studies have detected neural activity related to monetary loss. The receipt of monetary loss activates a broad range of brain regions, including the anterior cingulate cortex (ACC), inferior frontal gyrus, medial frontal cortex, insula, cuneus, lingual gyrus, and parahippocampal gyrus (García, Filbey, Dunlop, & Myers, 2013 ; Kocsel et al, 2017 , 2019 ; Lauwereyns, Bjork, Smith, Chen, & Hommer, 2010 ; Luo et al, 2019 ; Ubl et al, 2015 ; Yan et al, 2016 ; Yu, Duan, Wu, & Luo, 2021 ; Yu, Wu, Huang, & Luo, 2020 ). Moreover, a meta‐analysis of monetary loss found that the outcome of monetary loss consistently activated the striatum and anterior cingulate gyri (Dugré, Dumais, Bitar, & Potvin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have detected neural activity related to monetary loss. The receipt of monetary loss activates a broad range of brain regions, including the anterior cingulate cortex (ACC), inferior frontal gyrus, medial frontal cortex, insula, cuneus, lingual gyrus, and parahippocampal gyrus (García, Filbey, Dunlop, & Myers, 2013 ; Kocsel et al, 2017 , 2019 ; Lauwereyns, Bjork, Smith, Chen, & Hommer, 2010 ; Luo et al, 2019 ; Ubl et al, 2015 ; Yan et al, 2016 ; Yu, Duan, Wu, & Luo, 2021 ; Yu, Wu, Huang, & Luo, 2020 ). Moreover, a meta‐analysis of monetary loss found that the outcome of monetary loss consistently activated the striatum and anterior cingulate gyri (Dugré, Dumais, Bitar, & Potvin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%